2021
DOI: 10.3390/jcm10225317
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review of Gaps in the Diagnosis and Management of Drug-Induced Liver Injury Associated with Severe Cutaneous Adverse Reactions

Abstract: Drug-induced liver injury (DILI) encompasses the unexpected damage that drugs can cause to the liver. DILI may develop in the context of an immunoallergic syndrome with cutaneous manifestations, which are sometimes severe (SCARs). Nevirapine, allopurinol, anti-epileptics, sulfonamides, and antibiotics are the most frequent culprit drugs for DILI associated with SCARs. Interestingly, alleles HLA-B*58:01 and HLA-A*31:01 are associated with both adverse reactions. However, there is no consensus about the criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 126 publications
(163 reference statements)
0
3
0
Order By: Relevance
“… 5 Case reports of bupropion-induced liver injury have been documented, and liver injury in DRESS might be one variant of DILI as evidenced by our patient’s course. 6 , 7 …”
Section: Discussionmentioning
confidence: 99%
“… 5 Case reports of bupropion-induced liver injury have been documented, and liver injury in DRESS might be one variant of DILI as evidenced by our patient’s course. 6 , 7 …”
Section: Discussionmentioning
confidence: 99%
“…These reactions are commonly seen in cases of allopurinol liver injury accompanied by drug reaction with eosinophilia and systematic symptoms (DRESS syndrome) or Stevens Johnson syndrome/ toxic epidermal necrolysis (SJS/TEN). 19,20,[39][40][41][42][43] An included study showed hepatobiliary disorders were experienced in allopurinol groups only for cholestasis (0.6%) and hepatotoxicity (0.6%) and assessed as severe in intensity. These liver abnormalities did not appear in the febuxostat groups.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, aside from the causality assessment tools, there are no specific or collective tools available to evaluate SCARs in relation to liver injury. Because of this, less effective treatment for SCARs with systemic involvement may be chosen ( Villanueva-Paz et al, 2021 ).…”
Section: Future Perspectivementioning
confidence: 99%